Characterization and identification of extrachromosomal circular DNA in cholangiocarcinoma - Zar Zar Win; Hasaya Dokduang; Siriyakorn Kulwong; Watcharin Loilome; Nisana Namwat; Jutarop Phetcharaburanin; Thidathip Wongsurawat; Piroon Jenjaroenpun; Poramate Klanrit; Arporn Wangwiwatsin (PLoS ONE, 2025)
Extrachromosomal circular DNAs (eccDNAs) have gained attention as key players in cancer heterogeneity, potentially associated with elevated oncogene copy numbers in many cancers. While the presence of eccDNA in both normal and cancer cells is confirmed, its influence on gene-level alterations in cancer cells remains largely unexplored. This study delves into the genomic profiles of eccDNA in cholangiocarcinoma (CCA), an aggressive biliary tract cancer with extensive heterogeneity and diverse molecular alterations, using a modified long-read CircleSeq method. We reveal distinct eccDNA characteristics in CCA compared to non-tumor cells, focusing on genic components and chromosomal origins. Analysing read depth differences in oncogene-containing eccDNA; we identified potential eccDNA candidates that may be relevant for CCA biology. Subsequent bioinformatics analysis was performed using the established CReSIL tool, revealing distinct patterns of these oncogenes, particularly genes in the RAS/BRAF pathway, suggesting a potential functional role. These findings highlight the remarkable heterogeneity and diverse origins of eccDNA in CCA. This study establishes the first profiling of eccDNA in cholangiocarcinoma and paves the way for further investigation of its potential contribution to oncogene amplification and disease progression.